Correlation Between Risk Perception and Outcome Expectancies on Dietary Compliance in Diabetes Mellitus Patients - Arina Qona'ah; Nikmatul Fauziah; Gusmaniarti; Hikmah Lia Basuni (Babali Health, 2022)
Introduction: Diabetic patients' non-compliance with diet can increase the risk of complications and decrease quality of life. Dietary compliance can be influenced by motivation, self-efficacy, knowledge, intentions, and family support. This study aims to analyze the relationship between perceived risk and expected outcomes with dietary compliance in patients with type 2 diabetes mellitus. Methods: 150 respondents were obtained from five Primary Health Care in Surabaya through the cluster sampling method. The instruments used were a risk perception, a healthy diet-outcome expectation scale, and dietary compliance questionnaire. Data were analyzed using Spearman’s Rho statistics (α≤0.05). Results: Most of the patients had moderate risk perception (67.3%) and high outcome expectation (48%). There was a significant relationship between perceived risk (p = 0.000) and expected outcome (p = 0.000) with dietary compliance in type 2 DM patients. Conclusion: Diabetic patients' perceptions of their disease and the expected results have a positive effect on patient adherence to diet. Patients need accurate information about their disease so that they can create good perceptions and expectations.